Potential of volatile organic compounds in the management of insect pests and diseases of food legumes: a comprehensive review - Makhlouf, Leila; El Fakhouri, Karim; Kemal, Seid Ahmed; Maafa, Ilyas; Meftah Kadmiri, Issam; El Bouhssini, Mustapha (Frontiers in Plant Science, 2024)
Cool season legumes (Faba bean, chickpea, lentil, pea, and grass pea) are important protein harvests for food and nutrition security in many countries. They play key roles in sustainable cereal production through their ecological benefits. However, diseases and pests attack continue to have a substantial impact on crop yield and quality. Although growers used different control options to manage these biotic stresses such as pesticide application, cultural practices, and resistant varieties, there is a pressing need for the development of new, more cost-effective and environmentally friendly solution to help farmers in facing the existing environmental issues.The management of diseases and pests attacking food legumes remains a critical challenge that directly affects crop yield and quality. Pesticide application, cultural practices, biopesticides, natural enemies, resistant varieties and integrating two or more control options are used by growers to manage these biotic stresses.Recently, there is a growing interest among researchers in exploiting Volatile Organic Compounds (VOCs) for the elaboration of disease and pest control strategies in food legumes and other crops. These compounds have important functions in ecological relationships occurring between plants and their surrounding environment, as well as plants and others species, such as pests and pathogens. Due to their unique properties, VOCs can be employed to enhance plant development and protect plant from insect pest infestations and disease incursions. Due to the availability of low-cost sensor devices, VOCs can be incorporated into host plant resistance breeding programs and integrated pest control practices. In this assessment, we investigated the role of VOCs in improving management alternatives for food legume diseases and pests.In this assessment, we investigated the role of VOCs in plant-pest and plant-pathogen interactions and their present applications in pest and diseases control strategies. We emphasized the ecological importance of employing plant VOCs in legume farming and crop breeding. Additionally, we highlighted the potential of microbial VOCs in facilitating microbemicrobe, microbe-plant and microbe-plant-pest interactions, along with their role in food legume protection.